Anti-CD123 chimeric antigen receptor T-cells (CART): an evolving treatment strategy for hematological malignancies, and a potential ace-in-the-hole against antigen-negative relapse. Issue 7 (3rd July 2018) - Cummins, Katherine D.; Gill, Saar
Abstract: Chimeric antigen receptor-modified T-cells (CART) are a potent and targeted immunotherapy which have induced remissions in some patients with chemotherapy refractory or relapsed (RR) hematologic malignancies. Hundreds of patients have now been treated worldwide with anti-CD19 CART cells, with complete response rates of up to 90%. CART therapy has a unique toxicity profile, and unfortunately not all responses are durable. Treatment failure occurs via two main routes – by loss of the CART cell population, or relapse with antigen loss. Emerging data indicate that targeting an alternative antigen instead of, or as well as CD19, could improve CART cell efficacy and reduce antigen-negative relapse. Other strategies include the addition of other immune-based therapies. This review explores the rationale, pre-clinical data and currently investigative strategies underway for CART therapy targeting the myeloid and lymphoid stem/progenitor antigen CD123.